13m+5n-5m+11n=

Simple and best practice solution for 13m+5n-5m+11n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13m+5n-5m+11n= equation:


Simplifying
13m + 5n + -5m + 11n = 0

Reorder the terms:
13m + -5m + 5n + 11n = 0

Combine like terms: 13m + -5m = 8m
8m + 5n + 11n = 0

Combine like terms: 5n + 11n = 16n
8m + 16n = 0

Solving
8m + 16n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-16n' to each side of the equation.
8m + 16n + -16n = 0 + -16n

Combine like terms: 16n + -16n = 0
8m + 0 = 0 + -16n
8m = 0 + -16n
Remove the zero:
8m = -16n

Divide each side by '8'.
m = -2n

Simplifying
m = -2n

See similar equations:

| 15x-9=3x | | 9c+9.45=118.89 | | 1/4(8x-4)=10 | | 5(-7x-8)+3x=184 | | x-3x^(1/2)-18=0 | | 7z*2=9-3z | | 3cot^2x-6=0 | | 21x+28-2=10x+12 | | -x^3+20x+80=0 | | x-3x^(1/2)–18=0 | | 8x-32=14x-(2x+80) | | x+5+4x-60=90 | | 7.36x+16=54.1696+4x | | |1/3-2|=4 | | -z^3+20z+80=0 | | 6.7x+33.5=67 | | x-3x^(1/2)-2x^2–18=0 | | 4y-6=2y+y | | -6x-10y=5 | | X*9=36 | | .5x-5=0 | | (-x-2)*2= | | 4x-60-x+5=90 | | 6r^2-24=0 | | z^3-5z^2-16z=-80 | | 4x-60+x+5=180 | | -7/5x=28 | | (-x-2)= | | log(x^2)=8 | | 5-3(6-4x)=4+2(5x-3) | | 4x-60+x+5=90 | | (-x-2)2= |

Equations solver categories